Average BER of SIM-DPSK FSO System With Multiple Receivers over $ \mathcal {M}$-Distributed Atmospheric Channel With Pointing Errors - Nenad D. Milosevic; Milica I. Petkovic; Goran T. Djordjevic (IEEE Photonics Journal, 2017)
In this paper, an average bit error rate (BER) analysis of the free-space optical (FSO) system applying subcarrier intensity modulation with binary differential phase-shift keying is presented. Multiple receiver apertures are considered, when maximal-ratio combining (MRC) is employed. Intensity fluctuations due to atmospheric turbulence are modeled by M $\acute{{\rm {a}}}$ laga ( $ \mathcal {M}$ ) distribution, taking the pointing errors effect into account. Novel closed-form average BER expression is derived in terms of Meijer's G-function. Utilizing derived expression, numerical results are presented and confirmed by Monte Carlo simulations. The effects of atmospheric turbulence and pointing errors parameters, as well as the number of photodetectors, on the average BER performance are discussed. Employing multiple receivers with MRC leads to the improvement of the FSO system performance. Numerical results illustrate that this improvement depends on the FSO channel conditions. In addition, it is proved that SNR unbalance scenario can seriously deteriorate system performance.